An improved time-varying mesh stiffness model for helical gear pairs considering axial mesh force component. (June 2018) - Wang, Qibin; Zhao, Bo; Fu, Yang; Kong, Xianguang; Ma, Hui
Highlights: An improved time-varying mesh stiffness model for a helical gear pair considering axial mesh force component is proposed. The axial tooth bending stiffness, axial tooth torsional shear stiffness and axial gear foundation stiffness models are proposed. A rapid time-varying mesh stiffness calculation method is established, in which each stiffness components can be obtained by the integration along the gear width. Abstract: An improved time-varying mesh stiffness (TVMS) model of a helical gear pair is proposed, in which the total mesh stiffness contains not only the common transverse tooth bending stiffness, transverse tooth shear stiffness, transverse tooth radial compressive stiffness, transverse gear foundation stiffness and Hertzian contact stiffness, but also the axial tooth bending stiffness, axial tooth torsional stiffness and axial gear foundation stiffness proposed in this paper. In addition, a rapid TVMS calculation method is proposed. Considering each stiffness component, the TVMS can be calculated by the integration along the tooth width direction. Then, three cases are applied to validate the developed model. The results demonstrate that the proposed analytical method is accurate, effective and efficient for helical gear pairs and the axial mesh stiffness should be taken into consideration in the TVMS of a helical gear pair. Finally, influences of the helix angle on TVMS are studied. The results show that the improved TVMS model is effective for any helix angle and the traditional TVMS model is only effective under a small helix angle.